2018
DOI: 10.4039/tce.2017.66
|View full text |Cite
|
Sign up to set email alerts
|

Conserving carnivorous arthropods: an example from early-season cranberry (Ericaceae) flooding

Abstract: Biological control plays an important role in many integrated pest management programmes, but can be disrupted by other control strategies, including chemical and cultural controls. In commercial cranberry (Vaccinium macrocarpon Aiton; Ericaceae) production, a spring flood can replace an insecticide application, providing an opportunity to study the compatibility of the flood (a cultural control) with biological control. We suspect that chemical controls will tend to reduce the number of natural enemies, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The recently discovered nematode Oscheius onirici Torrini et al (Rhabditida: Rhabditidae) can kill S. sulfureana (Ye et al, 2018;Foye and Steffan, 2019) and A. vaccinii (Ye et al, 2018), as well as suppress S. frontalis (Foye and Steffan, 2019). Other predators that are commonly present in cranberry ecosystems include spiders (Bardwell and Averill, 1996;van Zoeren et al, 2018;de Lange et al, 2019b), staphylinid beetles (Haase-Statz, 1997, coccinellid beetles (Rodriguez-Saona et al, 2011a;Salamanca et al, 2017;de Lange et al, 2019b;Salamanca et al, 2019), chrysopid lacewings (Rodriguez-Saona et al, 2011a;de Lange et al, 2019b;Salamanca et al, 2019), and syrphid flies (Rodriguez-Saona et al, 2011a;Salamanca et al, 2017;de Lange et al, 2019b;Rodriguez-Saona et al, 2020c).…”
Section: Natural and Biological Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…The recently discovered nematode Oscheius onirici Torrini et al (Rhabditida: Rhabditidae) can kill S. sulfureana (Ye et al, 2018;Foye and Steffan, 2019) and A. vaccinii (Ye et al, 2018), as well as suppress S. frontalis (Foye and Steffan, 2019). Other predators that are commonly present in cranberry ecosystems include spiders (Bardwell and Averill, 1996;van Zoeren et al, 2018;de Lange et al, 2019b), staphylinid beetles (Haase-Statz, 1997, coccinellid beetles (Rodriguez-Saona et al, 2011a;Salamanca et al, 2017;de Lange et al, 2019b;Salamanca et al, 2019), chrysopid lacewings (Rodriguez-Saona et al, 2011a;de Lange et al, 2019b;Salamanca et al, 2019), and syrphid flies (Rodriguez-Saona et al, 2011a;Salamanca et al, 2017;de Lange et al, 2019b;Rodriguez-Saona et al, 2020c).…”
Section: Natural and Biological Controlmentioning
confidence: 99%
“…Flooding also has been prescribed throughout the year to control E. apiata, L. dispar, X. nupera, the white grub, Phyllophaga anxia LeConte (Coleoptera: Scarabaeidae), and the southern red mite, Oligonychus ilicis McGregor (Trombidiformes: Tetranychidae) (Averill et al, 1997). Additionally, early season flooding has been shown to increase natural enemy abundance, such as spiders and parasitoids (van Zoeren et al, 2018). Flooding is also used in IPM against certain weeds (Demoranville et al, 2005) and fungi (Averill et al, 1997).…”
Section: Cultural Controlmentioning
confidence: 99%
“…This high reliance on rented honey bees in both regions for cranberry pollination mirrors the broader reliance of many agricultural crops on managed bees for pollination (Klein et al, 2007), though growers in some systems, including apples and pumpkins (Park et al, 2020;McGrady, Troyer and Fleischer, 2020), have found that honey bees can be superfluous in terms of their effects on crop yield. Managed bees are brought to farms between 10-15% cranberry bloom in either region, which is calculated by growers dividing the number of open flowers on ten cranberry uprights by the number of flowers and buds on those uprights (van Zoeren and Guédot, 2018). In both regions, the majority of respondents report determining when to bring in managed pollinators by calculating the percent bloom themselves (57.14% WI, 81.82% QC).…”
Section: Pollination Practicesmentioning
confidence: 99%
“…The copyright statement for the article by van Zoeren et al . (2018) in the April 2018 issue of The Canadian Entomologist was incorrectly listed. The correct copyright should have appeared as follows, and has been changed in the original:…”
mentioning
confidence: 99%